Contributions of Stephen J. Ball to the research on educational and curriculum policies in Brazil (UCL Press, 2013)
This article aims at showcasing the main contributions of Stephen J. Ball to educational research in Brazil, particularly to the study of educational and curriculum policies. We also highlight some of the limitations in the incorporation of Ball's ideas in Brazil as well as some of the challenges that these author's ideas pose to Brazilian researchers. The article points out to the ability of Ball's work to inspire a critical analysis of educational and curriculum policies and of the outcomes and consequences of these policies to different social classes. Due to the richness and depth of Ball's work, the article indicates that it would be crucial for Brazilian researchers to explore a wider variety of Ball's texts, with the goal of understanding how he operates with the concepts and theories and how he develops his analyses. This task would also contribute to a better quality of research in Brazil, particularly for those researchers that already have been using Ball's work as a reference.